Good Neighbor Empires : Children and Cultural Capital in the Americas - Albarrán, Elena Jackson (Critical Latin America, 2025)
A class of child artists in Mexico, a ship full of child refugees from Spain, classrooms of child pageant actors, and a pair of boy ambassadors revealed facets of hemispheric politics in the Good Neighbor era. Culture-makers in the Americas tuned into to children as producers of cultural capital to advance their transnational projects. In many instances, prevailing conceptions of children as innocent, primitive, dependent, and underdeveloped informed perceptions of Latin America as an infantilized region, a lesser "Other Americas" on the continent. In other cases, children's interventions in the cultural politics, economic projects, and diplomatic endeavors of the interwar period revealed that Latin American children saw themselves as modern, professional, participants in forging inter-American relationships.